2022
DOI: 10.1182/blood.2021014716
|View full text |Cite
|
Sign up to set email alerts
|

The oral ferroportin inhibitor vamifeport improves hemodynamics in a mouse model of sickle cell disease

Abstract: Sickle cell disease (SCD) is an inherited hemolytic anemia caused by a single point mutation in the beta‑globin gene of hemoglobin that leads to synthesis of sickle hemoglobin (HbS) in red blood cells (RBCs). HbS polymerizes in hypoxic conditions, leading to intravascular hemolysis, release of free hemoglobin and heme, and increased adhesion of blood cells to endothelial vasculature, which causes painful vaso-occlusion and organ damage. HbS polymerization kinetics are strongly dependent on the intracellular Hb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 63 publications
0
29
0
Order By: Relevance
“…Owing to the central role of hepcidin in regulating iron homeostasis, compounds that either mimic or block its function are of high therapeutic interest, and several agents are currently in clinical development for the treatment of anemia or iron overload conditions in different disorders ( Casu et al, 2018 ; Crielaard et al, 2017 ; Katsarou and Pantopoulos, 2018 ). Among those agents, the first orally available FPN inhibitor vamifeport (VIT-2763) is now in clinical trials for the treatment of β-thalassemia and sickle cell disease ( Manolova et al, 2019 ; Nyffenegger et al, 2022 ). On the molecular level, vamifeport was shown to compete with hepcidin for FPN binding with an IC 50 value in the low nanomolar range ( Manolova et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Owing to the central role of hepcidin in regulating iron homeostasis, compounds that either mimic or block its function are of high therapeutic interest, and several agents are currently in clinical development for the treatment of anemia or iron overload conditions in different disorders ( Casu et al, 2018 ; Crielaard et al, 2017 ; Katsarou and Pantopoulos, 2018 ). Among those agents, the first orally available FPN inhibitor vamifeport (VIT-2763) is now in clinical trials for the treatment of β-thalassemia and sickle cell disease ( Manolova et al, 2019 ; Nyffenegger et al, 2022 ). On the molecular level, vamifeport was shown to compete with hepcidin for FPN binding with an IC 50 value in the low nanomolar range ( Manolova et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Here, we have investigated the interaction between human ferroportin (hsFPN) and its inhibitor vamifeport, which was shown to ameliorate anemia and iron homeostasis in a mouse model of β-thalassemia and is now in clinical development for this disorder and sickle cell disease (Manolova et al, 2019; Nyffenegger et al, 2022). Our study has provided two major novel results, it has revealed the conformational changes that lead to the transition of FPN from the familiar outward-facing into an occluded state, where the access to the substrate binding site is blocked from both sides of the membrane (Figure 3), and it has defined the binding site of vamifeport in the same occluded conformation (Figure 4).…”
Section: Discussionmentioning
confidence: 99%
“…Owing to the central role of hepcidin in regulating iron homeostasis, compounds that either mimic or block its function are of high therapeutic interest and several agents are currently in clinical development for the treatment of anemia or iron overload conditions in different disorders (Casu, Nemeth, & Rivella, 2018; Crielaard et al, 2017; Katsarou & Pantopoulos, 2018). Among those agents, the first orally available FPN inhibitor vamifeport (VIT-2763) is now in clinical trials for the treatment of β-thalassemia and sickle cell disease (Manolova et al, 2019; Nyffenegger et al, 2022). On the molecular level, vamifeport was shown to compete with hepcidin for FPN binding with an IC 50 value in the low nanomolar range.…”
Section: Introductionmentioning
confidence: 99%
“…Vamifeport (CSL Vifor) in 0.5% methylcellulose (Sigma Aldrich) was gavaged twice a day at 100 mg/kg. 32 PR73 was dissolved in SL220 (NOF Corp.) and injected intraperitoneally (i.p.) at 10 mg/kg twice per week.…”
Section: Inhibitor Studiesmentioning
confidence: 99%